Toward social-health integration in Sicily: description of the first hub and spoke model to improve the diagnostic therapeutic care paths for neurorehabilitation - De Cola, Maria Cristina; Ielo, Augusto; Lo Buono, Viviana; Quartarone, Angelo; Calabrò, Rocco Salvatore (Frontiers in Public Health, 2023)
The study describes a Hub and Spoke network for neuro-rehabilitation recently activated in Sicily, and evaluates the before-after changes yielded, in terms of integrated care. A set of indicators based on data contained in the administrative database of inpatients of the Regional Health System are presented and discussed. Statistical analysis was conducted both globally and separately for the 9 Sicilian provinces (Agrigento, Caltanissetta, Catania, Enna, Messina, Palermo, Siracusa, Ragusa, and Trapani). Results showed an increase in admissions of people residing in the province where the Spokes have been opened: Trapani (+ 32.4%), Messina (+ 7.8%) and Palermo (+ 4.4%); besides a significant increase of patients from healthcare facilities proportion (p = 0.001) and from acute wards (p = 0.029). In addition, we found a decrease of discharge to protected healthcare facilities (p = 0.001) and to acute wards (p < 0.001), as well as an increase of discharges to home (p = 0.018). In conclusion, it would seem that the activation of this network has facilitated the management of these patients, avoiding unnecessary migrations to other provinces and/or regions, and improving the regional care service for neuro-rehabilitation. Future research will be direct to investigate this aspect, focusing on before-after variations in hospitalization rates and origin-destination patient flows.